Dectin-1 Activation by a Natural Product β-Glucan Converts Immunosuppressive Macrophages into an M1-like Phenotype - Liu, Min; Luo, Fengling; Ding, Chuanlin; Albeituni, Sabrin; Hu, Xiaoling; Ma, Yunfeng; Cai, Yihua; McNally, Lacey; Sanders, Mary Ann; Jain, Dharamvir; Kloecker, Goetz; Bousamra, 2nd, Michael; et al. (The Journal of immunology (1950), 2015)
Tumor-associated macrophages (TAM) with an alternatively activated phenotype have been linked to tumor-elicited inflammation, immunosuppression, and resistance to chemotherapies in cancer, thus representing an attractive target for an effective cancer immunotherapy. In this study, we demonstrate that particulate yeast-derived β-glucan, a natural polysaccharide compound, converts polarized alternatively activated macrophages or immunosuppressive TAM into a classically activated phenotype with potent immunostimulating activity. This process is associated with macrophage metabolic reprograming with enhanced glycolysis, Krebs cycle, and glutamine utilization. In addition, particulate β-glucan converts immunosuppressive TAM via the C-type lectin receptor dectin-1-induced spleen tyrosine kinase-Card9-Erk pathway. Further in vivo studies show that oral particulate β-glucan treatment significantly delays tumor growth, which is associated with in vivo TAM phenotype conversion and enhanced effector T cell activation. Mice injected with particulate β-glucan-treated TAM mixed with tumor cells have significantly reduced tumor burden with less blood vascular vessels compared with those with TAM plus tumor cell injection. In addition, macrophage depletion significantly reduced the therapeutic efficacy of particulate β-glucan in tumor-bearing mice. These findings have established a new paradigm for macrophage polarization and immunosuppressive TAM conversion and shed light on the action mode of β-glucan treatment in cancer.